MENTORING PROCESS OF PRE-SERVICE TEACHERS DURING TEACHING PRACTICE - M. Nur Iqbal; Nuraeni . (ENGLISH, 2017)
This present study was aimed at investigating the mentoring process underwent by pre-service teachers during teaching practice, and the difficulties faced by them. The qualitative method was adopted, and interview and focus group discussion were used as the techniques of collecting data. Three pre-service teachers were selected as the participants of this study. The findings revealed that the pre-service teachers encountered different process of mentoring. Three of pre-service teachers experienced different frequency of mentoring, time, content, support and feedback of mentoring. The frequency of mentoring was done differently. The first pre-service teacher did the mentoring at any time if needed, the second one after the class finished, and the third one only three times during teaching practice. Regarding the time of mentoring, it was mostly done after the class finished, but sometimes only when the pre-service felt that the material was so difficult for their students. In the light of difficulties during the mentoring process, they faced five aspects; conflicting role expectation, compelled to emulate mentor, mentee exploitations, lack of constructive feedback, mentor distrust. The findings of this study contribute to the English Education Study Program particularly on the preparation for the students concerning teaching practice. They should be informed that mentoring is pivotal component that has to be faced during teaching practice.